Anatomic correction of simple transposition of the great arteries during the neonatal cardiovascular transition. Issue 7 (July 1984) - Lincoln, C R; Lima, R; Rigby, M L
Abstract : Complete 'anatomic' repair of transposition of the great arteries has now been achieved. The ideal timing of this surgery is during neonatal cardiovascular transition, when the fetal elevation of pulmonary vascular resistance is still present.